Parental concerns about their premature infants' health after discharge from the neonatal intensive care unit: a questionnaire survey for anticipated guidance in a neonatal follow-up clinic - Ji-Yun Cho; Juyoung Lee; Young Ah Youn; Soon Ju Kim; So Young Kim; In Kyung Sung (Korean Pediatric Society, 2012)
PurposeThe aim of this study was to develop an appropriate nursing information guideline according to corrected age, after investigating parents' concerns about the growth, development, and diseases of their premature infants after discharge from the neonatal intensive care unit (NICU).MethodsThe parents of premature infants (birth weight, <2,500 g; gestational age, <37 weeks) who went to a neonatal follow-up clinic after NICU discharge at Seoul St. Mary's Hospital from January 2005 to December 2009, were asked with regard to their concerns about their infants through a questionnaire survey. The results of physical examinations, including body measurements and neurodevelopmental status at 4, 8, 12, and 18 months of corrected age, were retrospectively reviewed in 390 infants.ResultsThe most common parental concerns were developmental delay, poor growth, and feeding and nutritional problems. Parental concerns about developmental delay, growth failure in improvement in body weight and length, and overweightness were high in specificity but very low in sensitivity. After NICU discharge, 30% of premature infants experienced infectious diseases before 18 months of corrected age, the most common of which was respiratory tract infection.ConclusionFor guiding of premature infants in outpatient day clinics after NICU discharge, it is necessary to identify the parents' highest concerns, to educate them about the possibilities of growth and neurodevelopmental disabilities in their infants and to provide them with handouts containing guidelines on the management of infectious diseases, especially respiratory infections.